Recent advances in the treatment of venous thromboembolism in the era of the direct oral anticoagulants [version 1; referees: 2 approved] - Jeffrey I. Weitz (F1000Research, 2017)
The direct oral anticoagulants (DOACs) have now supplanted vitamin K antagonists (VKAs) for the treatment of venous thromboembolism (VTE). The DOACs include dabigatran, which inhibits thrombin, and rivaroxaban, apixaban, and edoxaban, which inhibit factor Xa. The DOACs are as effective for the prevention of recurrence as conventional VTE treatment, consisting of a parenteral anticoagulant followed by a VKA, and are associated with less bleeding. Because of these properties and the convenience of fixed dosing without the need for routine coagulation monitoring, guidelines now recommend DOACs over VKAs for VTE treatment in patients without active cancer. This paper examines the increasing role of the DOACs for VTE treatment.